COMPARISON OF THE MODEL CRITICAL DISCOURSE ANALYSIS BY MILLS AND FAIRCLOUGH AT ONLINE MEDIA IN CASE REPORTING OF “IKAN ASIN” - Syarifa Rafiqa (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract: This study examines how the relationship between gender language and ideology is constructed in media texts, and aims to interrogate a small number of articles taken from the most widely read online editions of national newspapers in Indonesia regarding online media reporting on the harassment of women in the "Ikan Asin" case. The focuses of this research are 1) how the women are displayed in the text. 2) How media displays texts, discursive practices that include the production and consumption of texts, and social practices. 3) What are the differences between the Mills and Fairlough critical discourse analysis models? The results of the study are that women are displayed positively even though the case they experience is negative. Text production is closely related to the ideology of journalists and the media as well as the audiences who consume the text. Both Mills and Fairclough's critical discourse analysis models have similarities and differences in analyzing texts. Key Words: Critical Discourse Analysis, Mills, Fairclough, Ikan Asin.